Development of Students' Social Skills in Indonesia - Bito Reja Ninda Sari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Criticism of the school's disregard for the universal value of the knowledge it imparts and of its ability to guarantee the possibility of social mobility. This research aims to improve the development of students' social skills in Indonesia through digital comics. The research used was the 4D Research and Development Model from Thiaharajan and Semmel, namely Define, Design, Develop, Disseminate, which was carried out at SMA N 1 Padang Tualang with a total of 34 students. Data collection techniques use Observation, Questionnaires and Tests. Learning outcomes with data analysis techniques using Gain Score improve students' social skills. This research produces a product in the form of a digital comic that is suitable for use by fulfilling the Valid requirements as seen from the content suitability percentage of 83% in the very good category, presentation expert 61% in the good category, linguist expert 93% in the very good category.